2019
DOI: 10.13080/z-a.2019.106.020
|View full text |Cite
|
Sign up to set email alerts
|

In vitro tetraploid induction of the blackcurrant (Ribes nigrum L.) and preliminary phenotypic observations

Abstract: The aim of this study was to develop an in vitro polyploidisation method for the breeding of new improved cultivars of blackcurrant (Ribes nigrum L.). The Polish blackcurrant cultivars 'Gofert' and 'Polares' were used for the experiments. For polyploidisation, shoot explants were incubated for six days in the dark on a modified Murashige and Skoog medium supplemented with 4.5 µM 6-benzylaminopurine (BAP), 0.3 µM gibberellic acid (GA 3) and 0.5 µM indole-3-acetic acid (IAA), containing one of the following anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…During the last decade, meta -topolin has been widely used in micropropagation of many plant species, improving multiplication and rooting efficiency [ 41 , 42 , 43 ]. Our previous observation showed that the shoot of rhubarb ‘Malinowy’ treated with meta -topolin had higher rooting capacity than those cultured in BAP medium before rooting (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…During the last decade, meta -topolin has been widely used in micropropagation of many plant species, improving multiplication and rooting efficiency [ 41 , 42 , 43 ]. Our previous observation showed that the shoot of rhubarb ‘Malinowy’ treated with meta -topolin had higher rooting capacity than those cultured in BAP medium before rooting (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, we developed methods for the in vitro polyploidisation of daylily [14], apple [15], tulip [16] and blackcurrant [17]. In those methods, the shoots were treated with antimitotic agents such as colchicine, oryzalin, trifluralin and amiprophos methyl (APM).…”
Section: Introductionmentioning
confidence: 99%